Combined effect of brine salting and high-hydrostatic-pressure processing to improve the microbial quality and physicochemical properties of milkfish fillet. Issue 1 (31st December 2022) - Tsai, Yung-Hsiang; Kung, Hsien-Feng; Lin, Chung-Saint; Hwang, Chiu-Chu; Lou, Su-Shing; Huang, Chun-Yung; Chang, Sam K. C.; Lee, Yi-Chen
ABSTRACT: The effects of soaking milkfish fillet in 3% or 9% NaCl brines for 90 min at 4°C, and followed by processing with varying hydrostatic pressures (300, 400, 500, and 600 MPa) for 5 min on microbial quality and physicochemical properties were evaluated. After brine salting, the color of the fillet, the L* (lightness), W (whiteness), and ΔE (color difference) values increased with the increases in pressure, whereas the a* (redness) and b* (yellowness) values decreased, indicating that the fillet became brighter and whiter. Among them, 3% brine salting combined with pressures of 300 and 400 MPa groups had higher redness (a* value) and lower ΔE value compared to the higher pressure groups. Regarding the texture of the fillet, the hardness and chewiness of unsalted fish were significantly higher than that of brine salted fish under the same pressure, whereas the cohesiveness of the unsalted fillet was significantly lower than that of brine salted fillet. The results indicates that brine salting could make the instrumental texture of fish softer, which can compensate for the disadvantages of increased hardness and chewiness of the fillet caused by high-pressure processing. Brine salting combined with high pressure produced a significantly reducing effect on aerobic plate count (APC), psychrotrophic bacteria count (PBC), and total volatile basic nitrogen (TVBN) values of the fish as compared with that by brine salting or high pressure alone. Therefore, brine salting at a proper brine concentration (3%) and followed by high-pressure processing at 300 or 400 MPa for 5 min can improve or maintain a relatively good color and texture, as well as result in a synergistic bactericidal effect.